Disparities in Judges’ Decisions on Defamation Crimes via Social Media (A Study of Medan District Court Decisions Number 2040/PID.Sus/2022/PN.Mdn and Number 3563/PID.Sus/2019/PN.Mdn) - Saragih, Fitrah Anata; Trisna, Wessy; Tarigan, Vita Cita Emia (Universitas Islam Negeri Sumatera Utara, 2025)
This study discusses the disparity of judges' decisions regarding criminal acts of defamation through social media (Study of Medan District Court Decision Number 2010 / Pid.Sus / 2022 / PN.MDN, and Medan District Court Decision Number 3563 / Pid.Sus / 2019 / PN.MDN. This study uses a normative legal research type. The results of this study are that the legal regulation of this criminal act of defamation is regulated by Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning ITE, which is contained in Article 27 paragraph 3 which reads: Every person intentionally and without the right to distribute and / or transmit and / or make accessible Electronic Information and / or Electronic Documents that contain insults and / or defamation.